Integrated urban hydrologic and hydraulic modelling in Chicago, Illinois. (March 2016) - Zhu, Zhenduo; Oberg, Nils; Morales, Viviana M.; Quijano, Juan C.; Landry, Blake J.; Garcia, Marcelo H.
Abstract: With rapidly growing urbanization, urban flooding and water quality control are becoming a vital component of sustainable urban infrastructure. Integrated urban hydrologic and hydraulic modelling represents a potential framework for capturing system interactivity and optimizing the design, operation, and engineering of urban systems. This work describes how a widely-used hydrodynamic model, the Environmental Fluid Dynamics Code (EFDC), was made compliant with the Open Modelling Interface (OpenMI) standard. The new version of the EFDC has potential to be coupled with any OpenMI-compliant model for various studies. As an example, this paper presents an application of the OpenMI version of EFDC coupled with InfoWorks-CS for a representative highly urbanized area in the city of Chicago, Illinois, United States. The integrated modelling simulates the two-way linkage between the sewer network and the Chicago Area Waterway System (CAWS). This interaction between the river and sewer pipe systems can not be described by decoupled models. By coupling the models, it is possible to observe the interaction between the sewer system overflow discharge and the hydraulic head in the pipe network. This is particularly important since higher water levels in the pipe system increase the potential for flooding. Graphical abstract: